2015
DOI: 10.3389/fpsyg.2015.00561
|View full text |Cite
|
Sign up to set email alerts
|

Do semantic contextual cues facilitate transfer learning from video in toddlers?

Abstract: Young children typically demonstrate a transfer deficit, learning less from video than live presentations. Semantically meaningful context has been demonstrated to enhance learning in young children. We examined the effect of a semantically meaningful context on toddlers’ imitation performance. Two- and 2.5-year-olds participated in a puzzle imitation task to examine learning from either a live or televised model. The model demonstrated how to assemble a three-piece puzzle to make a fish or a boat, with the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 73 publications
3
21
1
Order By: Relevance
“…Based on the transfer deficit literature, we predicted that, following a ghost demonstration on the touchscreen, children would perform better when tested on a touchscreen than a magnet board. We also predicted that 3‐year‐olds would perform significantly better than 2.5‐year‐olds, as reported in previous studies using this task (Dickerson et al., ; Moser et al., ; Zimmermann et al., ).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Based on the transfer deficit literature, we predicted that, following a ghost demonstration on the touchscreen, children would perform better when tested on a touchscreen than a magnet board. We also predicted that 3‐year‐olds would perform significantly better than 2.5‐year‐olds, as reported in previous studies using this task (Dickerson et al., ; Moser et al., ; Zimmermann et al., ).…”
supporting
confidence: 78%
“…Many educational apps do not include social demonstrators, and instead display on‐screen objects that move by themselves. Young children demonstrate a transfer deficit , consistently learning fewer actions when they have to transfer learning from television and touchscreens to real‐world objects, compared to when no transfer is required (Dickerson, Gerhardstein, Zack, & Barr, ; Moser, Zimmermann, Grenell, Barr, & Gerhardstein, ; Zack, Barr, Gerhardstein, Dickerson, & Meltzoff, ; Zack, Gerhardstein, Meltzoff, & Barr, ; Zimmermann et al., ). Barnett and Ceci () define transfer as the application of information to a situation distinctly different from the condition in which it was learned and can be applied to conditions changing from 2D to 3D.…”
mentioning
confidence: 99%
“…While the debate as to the mechanisms underlying children's word learning goes on, it is clear that memory and language are linked from very early in development (Taylor, Liu, & Herbert, ; Zimmermann et al., ). In particular, learning a new word depends critically on children's ability to form and retain word‐object associations.…”
Section: Introductionmentioning
confidence: 99%
“…The current secondary data analyses included data drawn from five previously published studies using the puzzle imitation task (see Table ; Barr et al ., ; Dickerson et al ., ; Moser et al ., ; Zimmermann et al ., , ). A total of 355 (182 girls) typically developing 2‐, 2.5‐, and 3‐year‐olds (from two metropolitan areas) were included in the sample analysed in the secondary data analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The puzzle imitation task was developed to examine factors affecting transfer of learning from screen media. This task involved construction of a 3‐piece magnetic or virtual puzzle that formed either a ‘fish’ or a ‘boat’ (Barr et al ., ; Dickerson et al ., ; Moser et al ., ; Zimmermann et al ., , ; for review see Hipp et al ., ). Across different studies, this puzzle task has been demonstrated for 2‐ to 3‐year‐olds via video, on a touchscreen with 2D virtual puzzle pieces, and on a magnet board using 3D magnet pieces.…”
Section: Introductionmentioning
confidence: 99%